Factors Influencing the Use of Long-Term Contraceptive Methods at the Noemuti Health Center, North Central Timor District - Naibaho, Flora; Nastiti, Deasy Harini; Simanihuruk, Ramatian; Panjaitan, Tiolina Klara (International Journal Papier Advance and Scientific Review, 2024)
Examining the factors that influence the utilization of Long-Term Contraceptive Methods (MKJP) at the Noemuti Health Center in the North Central Timor District is the purpose of this research. The principal issue is the inadequate utilization of MKJP, one of the safest and most effective contraceptives.This research employed a quantitative methodology and a cross-sectional design. In 2021, the entire active family planning acceptor population at the Noemuti Health Center in North Central Timor Regency comprised the study population of 1,899 individuals. As indicated by the results, the proportion of the low education variable that utilized MHJP was 36.8%, whereas the high education variable accounted for 33.3%. In relation to the use of MHJP, the employment variable revealed that 43.9% of acceptors who were employed utilized MHJP, whereas the employment variable of those who were unemployed utilized MHJP. The statistical analysis indicated that age, occupation, and level of education did not have a statistically significant impact on the utilization of MHJP. Nevertheless, the hypothesis was validated as the statistical data revealed that mothers with a higher level of education exhibited a greater utilization of contraceptives. This research offers valuable insights that can be utilized to bolster the family planning initiative and promote greater utilization of MHJP in Puskesmas Noemuti, North Central Timor District.